An improved defect classification algorithm for six printing defects and its implementation on real printed circuit board images - Ismail, Ibrahim; Zuwairie, Ibrahim; Kamal, Khalil; Musa, Mohd Mokji; Syed Abdul Rahman, Syed Abu Bakar; Norrima, Mokhtar; Wan Khairunizam, Wan Ahmad (ICIC International, 2012)
Link to publisher's homepage at http://www.ijicic.org/